2021
DOI: 10.1038/s41598-021-85388-y
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene microplastic contamination versus microplankton abundances in two lagoons of the Florida Keys

Abstract: A microscopic study of microplankton in two coastal lagoons in the Florida Keys coincidently, and unexpectedly, revealed the widespread presence of high concentrations of polystyrene microplastic particles. The polystyrene particles were first observed in the second year of a 2-year study of phytoplankton communities, with peak densities in the spring/summer of 2019 at all ten sampling sites in the two lagoons. Polystyrene particle densities reached levels up to 76,000 L−1. The particles ranged in size from 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 71 publications
(92 reference statements)
0
10
1
Order By: Relevance
“…The concentration of 200 particles L −1 for the continuous treatment was chosen to represent a high-pollution scenario based on values found in polluted coastal ecosystems (e.g., up to 125 particles L −1 , Patterson et al, 2020, 360 particles L −1 , Chae et al, 2015, and 76,000 particles L −1 , Badylak et al, 2021). Values were chosen so that the corals had regular contact with the particles during the time of the experiment while still representing a realistic scenario.…”
Section: Microplastic Exposure Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of 200 particles L −1 for the continuous treatment was chosen to represent a high-pollution scenario based on values found in polluted coastal ecosystems (e.g., up to 125 particles L −1 , Patterson et al, 2020, 360 particles L −1 , Chae et al, 2015, and 76,000 particles L −1 , Badylak et al, 2021). Values were chosen so that the corals had regular contact with the particles during the time of the experiment while still representing a realistic scenario.…”
Section: Microplastic Exposure Treatmentsmentioning
confidence: 99%
“…The concentration of ~1850 particles L −1 for the pulse treatment was chosen to provide at least one particle per coral polyp in the 24 h incubation, based on a count of the number of polyps in a subset of corals (n = 1 per species), while not causing stress reactions or feeding saturation (>10,000 particles L −1 ; Clayton & Lasker, 1982;Hii et al, 2009). This concentration still lies within measured environmental particle concentrations in highly polluted waters (Badylak et al, 2021). For the long-term experiment, coral nubbins were kept in six 80 L tanks (three continuous treatment tanks and three pulse treatment tanks, i.e., microplastic-free control tanks).…”
Section: Microplastic Exposure Treatmentsmentioning
confidence: 99%
“…cells in the experiment ranged from ∼2 × 10 6 to ∼2 × 10 7 cells/mL, which is 2–3 orders of magnitude higher than the environmental concentration. Although no studies were conducted on the ratio of microplastic to Synechococcus sp., ratios of phytoplankton to microplastic particles varied between 10 –5 and 1 in a natural environment. ,, Polystyrene (PS) is one of the most abundant microplastics found in ocean systems, and the particle density of PS has been reported reach to 76,000 particles/L in polluted coastal regions . Accordingly, 2 × 10 5 particles/mL of PS MPs was selected, and the ratios of PS particles to Synechococcus sp.…”
Section: Methodsmentioning
confidence: 99%
“…21,47,48 Polystyrene (PS) is one of the most abundant microplastics found in ocean systems, 49−51 and the particle density of PS has been reported reach to 76,000 particles/L in polluted coastal regions. 21 Accordingly, 2 × 10 5 particles/mL of PS MPs was selected, and the ratios of PS particles to Synechococcus sp. in this study were between 10 −2 and 10 −1 .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…We chose PS and PE microparticles as model MPs [59] in our study because of their abundance in marine plastic contaminants. [6][7][8][9][10][60][61][62] Although past studies have reported that PS and PE microparticles when dispersed in bulk nematic LC phases cause tangential and radial orientations of LCs, respectively, at their surfaces, [63,64] comparisons of the interactions of these microparticles at LC interfaces have not been reported. We find that the relative organizations of the two types of microparticles at LC interfaces cannot be predicted from the results of prior studies of microparticles in bulk LC phases.…”
Section: Introductionmentioning
confidence: 99%